PANoptosis in urological diseases: molecular mechanisms, pathological roles, and emerging therapeutic opportunities - Di, Xin; Jin, Xin; Feng, Shuqiang; Li, Ranwei (Frontiers in Immunology, 2026)
PANoptosis, a recently identified inflammatory programmed cell death pathway, integrates features of apoptosis, pyroptosis, and necroptosis and is regulated by a macromolecular complex called the PANoptosome. This pathway extends beyond conventional single-mode death mechanisms, marked a significant advancement in cell death research. Its emerging role in the pathogenesis and progression of urological diseases—including acute and chronic kidney injury, prostate cancer, renal carcinoma, and testicular pathologies—is increasingly recognized. This review outlines the molecular mechanisms and regulatory networks underlying PANoptosis and emphasizes its dual role, both in promoting tissue damage and in driving antitumor immunity. In addition, we discuss novel diagnostic biomarkers and therapeutic strategies targeting key components of PANoptosis, including multi-omics-based biomarker screening, nanomaterial-mediated delivery systems, and combination therapies. Advances in technologies, such as single-cell sequencing and spatial transcriptomics, are expanding precision medicine approaches, positioning PANoptosis as a promising target for improving clinical outcomes in urological diseases.